Molecular dynamic simulation of asphaltene co-aggregation with humic acid during oil spill. (November 2015) - Zhu, Xinzhe; Chen, Daoyi; Wu, Guozhong
Graphical abstract: Highlights: Asphaltene (ASP) aggregation in water was 2-fold higher than at oil–water interface. The presence of LHA increased the ASP aggregation by 43–83% in bulk water. The presence of LHA decreased the diffusion coefficient of ASP by up to 61%. Size of ASP–LHA complex (1:1) was 4- and 13-fold larger than that of LHA and ASP, respectively. Parallel stacking was the most likely mode for ASP co-aggregation with LHA. Abstract: Humic acid in water and sediment plays a key role in the fate and transport of the spilled oil, but little is known about its influence on the aggregation of heavy oil asphaltenes which is adverse for remediation. Molecular dynamic simulation was performed to characterize the co-aggregation of asphaltenes (continental model and Violanthrone-79 model) with Leonardite humic acid (LHA) at the toluene–water interface and in bulk water, respectively, to simulate the transport of asphaltenes from oil to water. At the toluene–water interface, a LHA layer tended to form and bind to the water by hydrogen bonding which provided a surface for the accumulation of asphaltenes by parallel or T-shape stacking. After entering the bulk water, asphaltene aggregates stacked in parallel were tightly sequestrated inside the inner cavity of LHA aggregates following surface adsorption and structure deformation. Asphaltene aggregation in water was 2-fold higher than at the toluene–water interface. The presence of LHA increased the intensity of asphaltene aggregation by up to 83% in bulk water while relatively less influence was observed at the toluene–water interface. Overall results suggested that the co-aggregation of asphaltene with humic acid should be incorporated to the current oil spill models for better interpreting the overall environmental risks of oil spill.